Diagnosis, Assessment, and Treatment of Non-Pulmonary Arterial Hypertension Pulmonary Hypertension - Hoeper, Marius M.; Barberà, Joan Albert; Channick, Richard N.; Hassoun, Paul M.; Lang, Irene M.; Manes, Alessandra; Martinez, Fernando J.; Naeije, Robert; Olschewski, Horst; Pepke-Zaba, Joanna; Redfield, Margaret M.; Robbins, Ivan M.; et al. (Journal of the American College of Cardiology, 2009)
The 4th World Symposium on Pulmonary Hypertension was the first international meeting to focus not only on pulmonary arterial hypertension (PAH) but also on the so-called non-PAH forms of pulmonary hypertension (PH). The term “non-PAH PH” summarizes those forms of PH that are found in groups 2 to 5 of the current classification of PH, that is, those forms associated with left heart disease, chronic lung disease, recurrent venous thromboembolism, and other diseases. Many of these forms of PH are much more common than PAH, but all of them have been less well studied, especially in terms of medical therapy. The working group on non-PAH PH focused mainly on 4 conditions: chronic obstructive lung disease, interstitial lung disease, chronic thromboembolic PH, and left heart disease. The medical literature regarding the role of PH in these diseases was reviewed, and recommendations regarding diagnosis and treatment of PH in these conditions are provided. Given the lack of robust clinical trials addressing PH in any of these conditions, it is important to conduct further studies to establish the role of medical therapy in non-PAH PH.